Correlation of MRI Findings With Patterns of Visual Field Loss in Patients With Pituitary Tumors. Issue 3 (September 2019) - Kane, Emily J.; Ashton, David E.; Mews, Peter J.; Reid, Kate; Neely, Andrew; Lueck, Christian J.
Abstract : Background: Compression of the optic chiasm by pituitary tumors typically results in bitemporal hemianopia, implying that nasal retinal fibers are preferentially damaged. The reason for this is not clear. One theory suggests that nasal fibers are selectively vulnerable simply because they cross each other. This study investigated the "crossing theory" by correlating visual field (VF) loss with chiasmal elevation and with the degree of eccentric compression on MRI scans. Methods: Our hospital database was searched to identify patients with a) chiasmal compression by a pituitary tumor; b) documented preoperative evidence of VF loss; and c) preoperative MRI scan performed within 1 month of VF testing. Temporality and bitemporality indices were derived from pattern deviation VF plots. Elevations of the central and peripheral parts of the chiasm were obtained from MRI scans, from which the eccentricity of compression was calculated. Temporality indices and hemifield loss were compared with central chiasmal elevation, and nasal hemifield loss in each eye was plotted against eccentricity. Results: Eleven patients were suitable for analysis. The degree of bitemporal VF involvement was significantly correlated with elevation of the central chiasm ( P = 0.004). However, there was minimal involvement of nasal VFs, and no demonstrable increase in nasal field loss with increasing eccentricity of compression. Conclusions: This study provides support for the crossing theory. These findings will inform further finite element models of chiasmal compression. A larger, prospective study is planned.